Are codesigned programmes more difficult to implement? A qualitative study of staff perceptions on the implementation of a new youth mental health programme - Michelle Kehoe; Rick Whitehead; Kathleen deBoer; Denny Meyer; Liza Hopkins; Maja Nedeljkovic (Health Expectations, 2024)
Abstract Background Codesigned interventions are becoming more common in health services and, in particular, in the design and development of mental health programmes and interventions. However, previous research has established that the transition from codesign to implementation can experience several challenges and that this transition process has received little research attention. Objective The aim of this study was to explore the experience of staff members charged with the implementation of a codesigned intervention for young people and adolescents at risk of suicide. Setting and Participants Five staff members involved in the implementation of the new codesigned programme took part in semi‐structured interviews. Method The study involved qualitative evaluation of staff experiences during the implementation of a new child and youth suicide intervention. Interviews were analysed using reflexive thematic analysis. Results The analysis identified four themes of ‘disconnect’, ‘operational challenges, ‘service user’ and ‘being authentic’. ‘Disconnect’ captures the difficulties of implementing a codesigned programme which leads to ‘operational challenges’ in meeting broader expectations while ensuring the feasibility of the programme. The third theme, ‘service user’, captures the realisation that the young people accessing the new service were different to those involved in the codesign process. The final theme, ‘being authentic’, highlights how staff needed to be responsive and flexible while remaining true to the principles proposed in the codesign. Discussion This study yielded some valuable insights into the challenges around the implementation of a codesigned intervention, an under‐researched area. The findings suggest that adaption of the design may be necessary, if it is not informed by implementation constraints, making it necessary for the implementation team to be well‐briefed on the initial design and given plenty of time to make the necessary adjustments in a coproduction process. Limitations for the generalisation of the results include a small sample of staff and particular challenges that may be unique to this study. Conclusion The present study highlights that for health services undertaking codesign approaches, appropriate time and resources need to be considered for the implementation phase of an initiative, to ensure that there is effective translation from design to implementation and that new codesigned services can be effective within operational constraints. Patient and Public Contribution The authors would like to thank and acknowledge the young people with a lived‐experience and their carers who participated in the codesign process and research evaluation component of this study. We also wish to thank the clinical staff, peer workers and family peer workers who participated in the evaluation.